Natural ventilation in classrooms for healthy schools in the COVID era in Mediterranean climate - Gil-Baez, M; Lizana, J; Becerra Villanueva, JA; Molina-Huelva, M; Serrano-Jimenez, A; Chacartegui, R (Elsevier, 2021)
Indoor air quality in schools has a direct impact on the performance and wellbeing of students. In 2020, the health emergency required the reconsideration of ventilation conditions in indoor spaces, especially for educational buildings. This paper advances previous investigations to identify affordable, sustainable, and healthy designs for the refurbishment and new construction of schools, analysing the design parameters of the buildings and the indoor air quality in a representative sample of schools in the Mediterranean climate. The set of schools represents the regional composition regarding ages, daily scholar schedules and building designs. This study evaluates indoor CO2, TVOCs, PM 2.5 and PM 10, concentration profiles regarding indoor temperature, relative humidity, and occupation rates to identify adequate natural ventilation strategies. The results show a wide dispersion in CO2 concentrations, ranging between 4110 and 5366 ppm (peak values), TVOC mean concentration varies from 206.99 μg/m3 to 589.71 μg/m3 and particulate matter fractions ranging between 1.14 and 15.6 μg/m3 for PM 2.5 and 2.04 and 34.86 μg/m3 for PM 10 during the occupancy period. Concentrations are related to the effect of ventilation actions, the occupation rates and the metabolism of occupants. The combination of values shows how natural ventilation designs can assure adequate indoor air quality within comfort conditions under these mild climate conditions.